ORGANIZATION OF INDEPENDENT STUDENT WORK BASED ON STUDENT BLOGGING ACTIVITY - A. A. Gareyev; O. F. Shikhova; Yu. A. Shikhov (Образование и наука)
Introduction. Today, the students’ personality traits and increasing their motivation to self-development are the most complex and urgent problems in foreign language training at higher technical university and in the system of higher education in general. According to the authors, the technology of student blogging is a means for addressing these issues, despite the lack of research on its methodology. In that regard, there is a need for further studies on information and communication technologies (ICT) application by promoting independent student work. The aim of this paper is to present the developed model of organization of bachelors’ independent work through educational blogging; to fulfill educational potential and to prove the efficiency of ICTs application in education taking into consideration professional foreign language competence development of future specialists in tool making. Methodology and research methods. When designing the model, the basic considerations of the following methodological approaches were considered: competency-based, personal-oriented, activity-based, thesaurus, and qualimetric; the listed above approaches enable to realize the principles of individualization, professional orientation, integrity, self-organization and interactivity in the performed work. The method of group expert assessment, as the leading one in pedagogical qualimetry, was chosen as the main method in the research undertaken. The methods of modeling and pedagogical experiment were involved. Results and scientific novelty. The structure of professional foreign language competence (including communicative, cognitive and subject components) of future toolmaking bachelors is identified. The development of the competence formation model among students is described in detail: having studied independently the subject topic, the students post the material. Pedagogical conditions and didactic guidelines for the model realization are formulated. The developed model, unlike many other models based on using ICT in foreign language teaching, takes into account the necessity of professional orientation of students’ foreign language self-learning. The model involves the use of thesaurus approach to enrich the learner’s vocabulary; and qualimetric approach to identify the level of their professional foreign language competence development. The developed model and the technology of student blogging were successfully tested as a part of pedagogical experiment at M. T. Kalashnikov Izhevsk State Technical University in the 2016−2017 academic year. Practical significance. The materials of the present investigation can be useful for teachers to organize independent student work. The technology of student blogging can be generalized and adapted to a wider range of higher education training programs.